Application of Self-Potential Method in Mapping Leachate Flow Around Rasau Jaya Landfills, Kubu Raya Regency: Penerapan Metode Potensial Diri (Self Potential) dalam Memetakan Aliran Lindi di Sekitar TPA Rasau Jaya Kabupaten Kubu Raya - Kaharudin Kaharudin; Yudha Arman; Muhardi (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2023)
This study uses the self-potential method to map the leachate flow around the Rasau Jaya landfill, Sungai Raya District, Kubu Raya Regency. The study was carried out in 2 areas, the north and south of the landfill. Data acquisition using a fixed base configuration by applying ten lines. Each line has a length of 105 m with 5 m, and the distance between the porous pots is 5 m. The measurement results show that the potential value distribution at the first location is -19.62 mV to 8.44 mV, and the potential value at the second location is -55.50 mV to 23.26 mV. The interpretation shows that leachate accumulation from the landfill in the first area has a potential value of -19.62 mV to -13 mV. The second location has a potential value of -55.50 mV to -36 mV. Based on isopotential contour maps, leachate accumulation in the first location is thought to be in the north to northeast of the landfill, while in the second location, it is thought to be in the southwest to the west of the landfill.